Perancangan Aplikasi Surat Perintah Tugas Melaksanakan Perjalanan Dinas Berbasis Web - Hendry Hendry; Eka Putra; Muhammad Zen; Supiyandi Supiyandi; Chairul Rizal (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Good management in conducting business trips has a positive effect on employees who take business trips and also on the smooth operation of the company. There are so many business travel destinations that are financed directly by the company such as: Business visits, parties, general meetings, educational and training activities as well as socialization. The method used by the author in this study is the Waterfall method which consists of: Requirements, Design, implementation, Verification and Maintenance. The result of this research is to produce an information system for official travel orders that will assist employees in the process of submitting a letter of assignment and the process of calculating official travel costs.